Dinâmica evolutiva do nicho ecológico em mamíferos - Mendoza Rodriguez, Victor Hugo (2020)
The different environmental conditions and the evolutionary history of each region prevent a homogeneous species distribution worldwide, creating the observed richness and diversity pattern. What allows two species to share the same habitat? What allows species to settle in certain places than in others on the planet? At this thesis, I contrasted phylogenetic history versus functional information for 4480 terrestrial and marine species of extant mammals in three ecological niche scales that correspond to Robert H. Whittaker's hierarchical biodiversity scales: α (local), β (regional) and γ (geographic). Thus, Niche α includes the competition dynamics. Niche β, represents the environmental filters on the communities and niche γ is the geographical space represented by the biogeographical realms where species occur. In the first chapter, I partitioned the three niche scales to assess evolutionary dynamics within scales, expected an evolutionary gradient, with the α scale as the most evolutionary labile, and the γ scale as the most conserved. For all species, I gathered ecological traits of diet, diel activity, and strata use for the α scale, environmental tolerances, and habitat types, for the β scale, and for the biogeographic realm where each species occurs the γ scale. I correlated the traits at each scale with phylogenetic distance for all mammals and subsequently for seventeen individual orders. Contrary to expectations, the α scale showed higher evolutionary divergence, suggesting the most conservative dynamics and the β scale the most labile. In the second chapter, I analyzed how the evolutionary dynamics of the niche scales are structured in the global geographic space. I expected more evolutionary conservatism in tropical latitudes at all three scales and higher lability as they approach the poles, both in terrestrial and marine species. Terrestrial mammals exhibited the expected pattern; however, marine species showed the opposite pattern, with a higher conservatism in high latitudes. In the third chapter, I explored the evolutionary dynamics of niche scales concerning critical climatic variables (low temperatures, high elevations, and low availability of water energy) versus regions with stable conditions. I expected differential environmental filtering for α, β, and γ scales, where species with similar niches converge under similar environmental conditions. Finally, as a fourth chapter, I carried out a systematic mapping about the Great American Biotic Interchange (GABI), analyzing the Spatio-temporal trend of the scientific literature, identifying the most relevant countries and institutions in scientific production for this topic.